EKSISTENSI PENGADILAN HAM DALAM PENANGANAN PELANGGARAN HAM APARAT PENEGAK HUKUM TERHADAP KELOMPOK KRIMINAL BERSENJATA DI PAPUA: EXISTENCE OF HUMAN RIGHTS COURTS IN HANDLING HUMAN RIGHTS VIOLATIONS BY LAW ENFORCEMENT OFFICERS AGAINST ARMED CRIMINAL GROUPS IN PAPUA - Tulia, Arter Lukas (Fakultas Hukum Universitas Trisakti, 2025)
The protection of the rights of life of humans is part of the category of non-derogable rights, namely rights that cannot be reduced. the existence of a separatist movement or KKB in Papua is considered an act of human rights violation, but in handling it through law enforcement officials resulted in not a few KKB members losing their lives, which for these actions is also a gross human rights violation. To analyze and find out about gross human rights violations by law enforcement officials against KKB members in Papua and the role and existence of the Human Rights Court in handling gross human rights violations. This research uses normative juridical legal research methods, because the topic studied can be resolved through analysis of secondary data or literature sources, without requiring primary data collection. The right to life in its regulation is contained in the provisions of the 1945 Indonesian Constitution, Law Number 39 of 1999 and Law Number 12 of 2005. The existence of the KKB in Papua is in fact a violation of human rights, but its handling by law enforcement officials, in fact, is not carried out through legal procedures, namely through the process of investigation, prosecution and court hearings, but unscrupulous law enforcement officials have in fact taken action to violate human rights by eliminating the lives of several KKB members. the existence of a human rights court until now has not optimally carried out its function to take action and prosecute the perpetrators of human rights violations both KKB members and law enforcement officials involved in eliminating the lives of several KKB members.